Phototypology as a method of displaying the formation of the urban environ-ment in a modern photobook - Safronova, Anna; Safronova, Olena; Safronov, Valeriy (Theory and practice of design, 2022)
Purpose. To figure out the directions of development and origins of the modern photonbook on the examples dedicated to the effect of the Soviet culture on the formation of the post-Soviet urban environment. Methodology. In the process of research, the following methods were used: art analysis, analysis of theoretical and historical preconditions for the development of the typology of a modern photobook that displays the urban environment; synthesis, generalization and systematization of the received information; methods of induction, deduction and comparative analysis. Results. It is shown that photobooks, dedicated to the influence of Soviet heritage on the formation of urban environment and landscape, continue the traditions established by the Dusseldorf School of Photography with some differences affected by the rise of publishing and design technologies. It is determined, that the characteristic feature of a modern photobook is a wider freedom in the choice of the target objects, angles of view, shots. But the concept of documenting the same or similar objects remains. Minimalism in the design of the indoor unit and cover, concise use of several options for repeating modular grids - the trends that unite the latest published photobooks. Scientific novelty. Typological features and principles of the design of one of the actual directions of the modern photobooks are revealed, which tend to continue the traditions of photographic typology as a form of presenting a photo project. Distinctive features in the formation of the design of such photobooks, associated with the development of modern digital technologies of photography and layout, are defined. Practical significance. A retrospective art analysis of photobooks, dedicated to the reflection of the urban environment, was conducted. The research is an important link in the further study of the history of the development of the photobook, as the implementation of the creative project of the photographer.